Promising vulnerability markers of substance use and misuse: A review of human neurobehavioral studies. (1st April 2021) - Lees, Briana; Garcia, Alexis M.; Debenham, Jennifer; Kirkland, Anna E.; Bryant, Brittany E.; Mewton, Louise; Squeglia, Lindsay M.
Abstract: Substance use often begins, and noticeably escalates, during adolescence. Identifying predictive neurobehavioral vulnerability markers of substance use and related problems may improve targeted prevention and early intervention initiatives. This review synthesizes 44 longitudinal studies and explores the utility of developmental imbalance models and neurobehavioral addiction frameworks in predicting neural and cognitive patterns that are associated with prospective substance use initiation and escalation among young people. A total of 234 effect sizes were calculated and compared. Findings suggest that aberrant neural structure and function of regions implicated in reward processing, cognitive control, and impulsivity can predate substance use initiation, escalation, and disorder. Functional vulnerability markers of substance use include hyperactivation during reward feedback and risk evaluation in prefrontal and ventral striatal regions, fronto-parietal hypoactivation during working memory, distinctive neural patterns during successful (fronto-parietal hyperactivation) and failed response inhibition (frontal hypoactivation), and related cognitive deficits. Structurally, smaller fronto-parietal and amygdala volume and larger ventral striatal volume predicts prospective substance misuse. Taken together, the findings of this review suggest that neurobehavioral data can be useful in predicting future substance use behaviors. Notably, little to no research has empirically tested the underlying assumptions of widely used theoretical frameworks. To improve the reliability and utility of neurobehavioral data in predicting future substance use behaviors, recommendations for future research are provided. This article is part of the special issue on 'Vulnerabilities to Substance Abuse.' Highlights: Substance use often begins, and noticeably escalates, during adolescence. This review summarizes neural and cognitive vulnerability markers of substance use. Aberrant prefrontal and striatal structure and function predicts escalating use. Executive functioning deficits increase vulnerability to substance use. Prevention initiatives should target these neural networks and cognitive functions.